Optical millimeter wave generation utilizing stimulated brillouin scattering for radio over fiber system - M.M.H Husaini; C.B.M Rashidi; SN Azemi; S.A Aljunid; M.S Anuar (Institute of Advanced Engineering and Science, 2019)
Optical millimeter-wave signal generation in Radio over Fiber (RoF) based on external modulators using different modulation schemes such as Single-Sideband (SSB), Double-Sideband (DSB) are experimentally compared. The major fallout for external modulation scheme system performance to downgrade is due to dispersion and the fading effect in optical signal generation while generating high Bit Error Rate (BER) when involving long distance delivery. In this work, we proposed mm-wave signal utilize Stimulated Brillouin Scattering (SBS) scheme which indicates the best performance amongst the scheme based on simulation that it achieves to propagate longest of distance over fiber, highest receiver sensitivity, the lowest BER and coherence of Mach-Zehnder Modulator (MZM) extinction ratio. Mm-wave signal of 40 Ghz and 10 Gb/s data rate was generated with the plotting of eye diagram.